On Word ‘Fake’ and What Is Behind It - Luciński, Kazimierz (Respectus Philologicus, 2015)
The paper focuses on a loanword borrowed from the English language “fake” that became very popular in the Russian soil. The author shows the derivational abilities of a word leading to the formation of new words that belong to the other parts of speech: a verb “фейковать”, an adjective “фейковый”, a noun “фейковость”. Every part of speech is analysed on the basis of paradigmatic relations, in which the word is involved, along with its sociolinguistic characteristics such as the field of use and social strata to which the native speakers belong. The author does not limit himself to an ordinary linguistic description of this loanword and its sense-correlates; instead the author tries to present socio-cultural peculiarities of reality that made possible a wide use of this loanword borrowed from the English language.